A Conservative Approach to Surgical Management of Root Canal Perforation - Régis Augusto Aleixo Alves; André Luiz Gomide Morais; Thábata Frederico Izelli; Cyntia R. A. Estrela; Carlos Estrela (Case Reports in Dentistry)
This study describes a conservative approach to surgical management of root canal perforation in maxillary lateral incisors. A patient was referred for retreatment of a maxillary lateral incisor. Her chief complaint was discomfort in the buccal mucosa. Periapical radiography showed radiopaque material consistent with sealing material inside the root canal. A CBCT scan was acquired and revealed a gutta-percha cone outside the root canal, from the middle third to beyond the root apex. The imaging examination showed that the pulp cavity had not been affected. Thus, we took the clinical alternative of surgically managing the perforation by sealing with MTA, thereby avoiding endodontic treatment, and followed up with only clinical and radiographic control. At the two-year follow-up, after the surgical procedure to remove the extruded filling material, we observed bone tissue formation and positive response to pulp tests, without any clinical signs or symptoms. Root perforation is considered an unpleasant error in an operative procedure. Once a perforation is properly diagnosed, located, and sealed with biomaterial, a favorable prognosis is often achieved. MTA offered good sealing of the perforation, with promising results. Decision-making using the CBCT scan enabled us to adopt a conservative approach and favored more reliable treatment predictability.